Mitigation of solar ultraviolet-B radiation induced photoinhibition in photochemistry and photosynthesis of rice (Oryza sativa L.) - Shafeeqa T. (Department of Plant Physiology, College of Horticulture, 2016)
Sun light contains ultraviolet (UV) radiation which is separated in to UV-C (100-280nm),UV-B (280-320 nm) and UV-A (320-400nm). Evidences from data collected from both satellite and field experiments indicated an increase in UV-B radiation reaching on the earth surface, due to decrease in ozone layer. Hence, UV-B has become more challenging nowadays causing threat to agriculture production in tropics. UV-B exclusion and enhancement studies conducted in the Department of Plant Physiology, College of Horticulture, Vellanikkara have revealed a decline in rice yield due to UV-B radiation in rice varieties Jyothi and Uma (Wagh, 2015). The present study entitled “Mitigation of solar ultraviolet-B radiation induced photoinhibition in photochemistry and photosynthesis of rice (Oryza sativa L.)” was conducted during 2014-2016 in the Department of Plant Physiology, College of Horticulture, Vellanikkara with the objective to understand the photo protective potential of ecofriendly stress mitigating chemicals on photoinhibition and photosynthesis of rice (Oryza sativa L.) under solar ultraviolet- B radiation. The pot culture experiment was conducted during November 2015 to March 2016 with rice variety Uma under two growing conditions viz. open condition- where the crop exposed to 100% solar radiation and polyhouse condition- which transmit 20% reduced full spectrum solar radiation including UV-B. Three ameliorative chemical treatments with two concentrations such as glycine betaine (10ppm and 20ppm), ascorbic acid (50ppm and 100 ppm) and combination fungicide 25WG trifloxystrobin + 50 WG tebuconazole (Nativo 75 WG- 50ppm and 70ppm) were given as foliar application at 30th and 60th DAT and observations were taken 15 days after each chemical spraying. The experiment was laid out as completely randomized design (CRD). The UV-B and Photosyntheticaly Active Radiation (PAR) in both conditions were monitored regularly throughout the crop period. The data on UV-B and PAR revealed significantly higher UV-B (2.18 Wm-2) and PAR (1786 μmolm-2s-1) during March-2016 under ambient condition. All growth phenophases were delayed under 100% solar radiation. Combination fungicide 25 WG trifloxystrobin+50WG tebuconazole 70ppm enhanced grain filling period under both the growing condition compared to other chemical treatments; the ultimate realization being a relatively good yield. Gas exchange parameters like photosynthetic rate, stomatal conductance and transpiration rate decreased during reproductive phase under 100% solar radiation, where the crop experienced high UV-B radiation. Among chemicals, 25 WG trifloxystrobin+50WG tebuconazole 70ppm enhanced the above parameters by alleviating the photoinhibition in photosynthesis and PSII activities. Photochemical efficiency as indicated by high Fv/Fm ratios was enhanced by foliar application of 25 WG trifloxystrobin+50WG tebuconazole 70ppm. High chlorophyll content, catalase activity and xanthophyll content were observed under reduced UV-B condition. Among chemical treatments significantly higher chlorophyll content was recorded for the rice plants treated with 25 WG trifloxystrobin+50WG tebuconazole 70ppm and this might be the reason for the increased photosynthetic rate in plants due to its application. The maximum yield contributed by 25 WG trifloxystrobin+50WG tebuconazole 70ppm may be due to the enhancement in thousand grain weight and number of spikelet per panicle, more photosynthetic rate and less fluorescence emission / increased photochemical efficiency of PS II, more chlorophyll content, catalase activity and reduction in the synthesis of secondary metabolites like flavanoid and xanthophylls. The ameliorative effect of this chemical has to be explored under field level for better results and recommendation to farmers for raising 3rd crop during puncha season.